Keefektivan padi transgenik terhadap hama penggerek batang padi kuning Scirpophaga incertulas (Walker) (Lepidoptera: Crambidae) - N. Usyati; Damayanti Buchori; Syafrida Manuwoto; Purnama Hidayat; Inez H. Slamet -Loedin (Perhimpunan Entomologi Indonesia, 2009)
Transformation two cry genes (cryIB-cryIAa) and transformation with a single the cry1B gene under the control of a wound-inducible maize proteinase inhibitor gene (mpi) promoter were two approaches that were used to get resistant rice to the rice stemborer which may be had a durable resistance. To obtain information on the effectiveness of seven transgenic rice lines to the rice yellow stemborer S. incertulas, a test was conducted in greenhouse. The seven lines were 1). line 4.2.3 and 2) line 4.2.4 both contain fusion of two cry genes (cryIB-cryIAa); 3) line 3R9 and 4) line 3R7 lines both contain of mpi-cryIB gene; and 5) line 6.11 contains of cryIAb gene by particle bombardment, 6) line DT-cry (Azygous) that do not contain cry gene (null), and 7) DT-cry line contains cryIAb gene by Agrobacterium, and as a negative control, we used three non transgenic rice varieties i.e., Rojolele, Cilosari, and Ciherang. The result showed that transgenic rice lines, except DT-cry and DT-cry (Azygous) lines were effective to suppress damage by the insect, and showed an inhibition effect on the growth of S. incertulas, and had a high level ofresistance than non transgenic rice varieties had. There were differences on resistance value/level among transgenic rice lines. Based on the resistance value, 6.11 line was the highest followed by 4.2.4 line and 3R7 line, these lines were categorized as high resistance. Transgenic rice-4.2.3 line and 3R9 line were categorized as moderat resistance. DT-cry and DT-cry (Azygous) lines were susceptible.